Examining women's career progression barriers - Tasnuva, Alam (2018)
It is been half a century women’s progression in professional career has been in a debate. Yet today, only scant percent of women are able to make their way at leadership and decision making positions at higher education institutions across the globe. However, women career in higher education has been of little concern to researchers. The purpose of this study is to examine the relationship between gender stereotype, work-family conflict, social-cultural beliefs, individual characteristics and organizational support with women’s career progression barriers among female staffs in a public university in Malaysia. This quantitative approach research has collected data from 264 female staffs of a public university using questionnaire survey. The study analyzes collected data utilizing Pearson correlation and multiple regression model to identify the relationship and test the hypothesis. The findings of the study reveal that gender stereotype, work-family conflict, and organizational support significantly influence the career progression barriers of female staffs. On the other hand, social-cultural beliefs and individual characteristics found to have an insignificant association, thus it does not affect career progression barriers of women staffs. This finding is believed to be logical in the context of Malaysia since it is a very inclusive and liberal nation. Finally, the study suggests that parental care leaves, childhood lessons and security (both social and physical) could be considered in analyzing in the future study.